Geoelectric prospecting in University Campus region for detection of possible geological discontinuities, Rio, Patra, Greece. - Angelis, L. G.; Stephanopoulos, P.; Papamarinopoulos, P. St. (Bulletin of the Geological Society of Greece, 2013)
Geophysical prospecting is a non catastrophic technique, applicable on a wide range of problems, including archaeological, environmental and geological problems. At Campus University of Patras, a detailed geophysical investigation applied for detection of possible existing geological discontinuities, which produced serious problems at buildings and main roads of Campus. As main technique used the electric mapping and electric imaging. These were applied on already prepared geophysical grids by measuring parallel profiles along and perpendicular to the geomagnetic north. The two geophysical grids were separated 100 meters away each other. Firstly, an electric mapping procedure took place by using twin-probe array with four electrodes in distance between 0.5-3 meters. As result was the recording of soil resistance on horizontal layer with constant depth. By processing the data through Geosoft Oasis Montaj software, the distribution of this physical property was illustrated on color scale maps. Secondly, electric imaging technique applied with twenty-five equal space electrodes along straight lines, with one meter space by using the hybrid arrangement Wenner-Schlumberger (Stephanopoulos, 2002). As result was the recording of distribution of soil apparent resistivity on a vertical layer in eight separated depths. Resistivity calculated by processing imaging data through 2D mathematical algorithm based on least squares inversion (Res2Dinv). Further processing by Oasis Montaj, had as a result the production of horizontal slices (Stephanopoulos 2002) and 3D maps, where the resistivity distribution was illustrated on separated depths, in color and grey schedule format. The combined geophysical investigation with the contribution of the HVSR (Horizontal to Vertical Spectral Ratio) technique confirmed the existence of geological discontinuity.